EFFECTS OF QUALITY OF WORK LIFE (QWL) AND ORGANIZATIONAL COMMITMENT (OC) ON ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) OF PERMANENT NURSES - Nadia Tri Hastuti; Ugung Dwi Ario Wibowo (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2021)
This research aims to identify the effects of quality of work-life and organizational commitment on organizational citizenship behaviour of permanent nurses. The research method is quantitative with 50 research subjects consisting of permanent nurses. The data were collected using Likert scale, consisting of organizational citizenship behaviour scale, quality of work-life scale, and organizational commitment scale. The scale of organizational citizenship behaviour has the reliability of 0.854, the scale of quality of work-life has the reliability of 0.933, and the scale of organizational commitment has the reliability of 0.901. Multiple linear regression was used as the analysis method. The research result reveals that the variable of quality of work-life significantly affects the variable of organizational citizenship behaviour. Moreover, the variable of organizational commitment also significantly affects the variable of organizational citizenship behaviour. Meanwhile, the variable of quality of work-life and organizational commitment simultaneously have significant effects on the variable of organizational citizenship behaviour.